Evaluasi Evaluasi Implementasi Scrum dengan SMM dan AMM: Studi Kasus Perusahaan Telekomunikasi PT XYZ: - Atissalam, Lintang Wisesa; Aji, Rizal Fathoni (AI Society & STMIK Indonesia, 2024)
PT XYZ is a telco company with more than 34.3 million users in Indonesia. PT XYZ adopted the Scrum framework in 3 projects of MyXYZ application development. The percentage of completion of each project in each sprint during the last year didn't reach 100%. This indicates there are problems in each sprint that could be slow down the release time of the newest feature and waste higher revenue potential. The Scrum Maturity Model is used to measure the maturity level of Scrum implementation. Data collection was carried out using the Scrum Assessment Questionnaire which consists of 70 questions. The questionnaires were given to 1 Scrum Master, 2 Product Owners and 4 Development Team members from each project. The data was then analyzed using the Agile Maturity Model key process area rating. As a result, Scrum implementation at PT XYZ is at level 3. Standardization and disciplined implementation of Scrum retrospectives are needed to be able to raise the maturity level to the next level.